2014
DOI: 10.1503/cjs.017712
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a novel night float call system: resident satisfaction and quality of life

Abstract: Background: Compliance with Professional Association of Internes and Residents ofOntario duty hour guidelines has been problematic at our institution. To facilitate orthopedic residents' ability to go home postcall without significant disruption of ongoing clinical activities, a novel call system was adopted at our tertiary care centre. We sought to evaluate the satisfaction and quality of life of orthopaedic residents with that system. Methods:We administered questionnaires to on-service residents. These incl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…However, with the introduction of the NF system in 2017, the average working time was maintained at 70–80 hours per week. A reduction in working hours has been shown to not only improve quality of life [16], but also allows more time for studying and publishing research papers [17], as well as more time to spend with their families [18]. Regarding concerns related to resident training quality, reports have shown that the number of surgical cases experienced by surgical residents has not changed after implementation of working hour restrictions [19].…”
Section: Discussionmentioning
confidence: 99%
“…However, with the introduction of the NF system in 2017, the average working time was maintained at 70–80 hours per week. A reduction in working hours has been shown to not only improve quality of life [16], but also allows more time for studying and publishing research papers [17], as well as more time to spend with their families [18]. Regarding concerns related to resident training quality, reports have shown that the number of surgical cases experienced by surgical residents has not changed after implementation of working hour restrictions [19].…”
Section: Discussionmentioning
confidence: 99%
“…Suffering and pleasure at work are analyzed in several studies, and research investigations on QWL have many advantages for both the company and the employees, as they reveal weaknesses and strengths in their activities, allowing them to implement measures to make it more enjoyable for workers. There is, therefore, increased in productivity, more competitiveness and more positive image to society (12)(13)(14)(15)(16)(17)(18) .…”
Section: Discussionmentioning
confidence: 99%
“…In this direction, organizational support will depend on how employees perceive the recognition given by the company to their work. This perception is influenced by the frequency, intensity and sincerity of praise and approval relations (13)(14)16,(23)(24) .…”
Section: Discussionmentioning
confidence: 99%
“…Duty hour restrictions have led many programs to implement night float systems so as to avoid long stretches of continuous hours working overnight on call and minimize duty hour violations. 11 Such innovative schedules have led to improved resident satisfaction and quality of life, 12 and some data indicate residents perceive quality of care to be higher with a night float system. 13 On the other hand, eliminating overnight call has also compromised clinical exposure in some training settings 14 and may actually be detrimental for trainee sleep.…”
Section: Discussionmentioning
confidence: 99%